1996
DOI: 10.1182/blood.v88.5.1747.bloodjournal8851747
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of P-glycoprotein in the transmembrane transport of interleukin-2 (IL-2), IL-4, and interferon-gamma in normal human T lymphocytes

Abstract: The physiological role of the multidrug resistance P-glycoprotein (P- gp), which is expressed by normal human T lymphocytes, is still largely unknown. To investigate whether or not P-gp is involved in the transport of cytokines, peripheral blood lymphocytes were stimulated with phytohemagglutinin (PHA) in the absence or presence of P-gp inhibitors, and concentrations of cytokines (interleukin-2 [IL-2], IL- 4, IL-6, interferon-gamma [IFN-gamma]) in the supernatants of these cultures were quantitated by enzyme-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 0 publications
2
64
0
1
Order By: Relevance
“…(2001) demonstrated that the pentoxyfilline (an inhibitor of TNF‐ α production) prevented the loss in biliary elimination of rhodamine123 after administration of K. pneumoniae endotoxin. Alternatively, endogenous compounds that are substrates for P‐gp including inflammatory cytokines and corticosterone (Wolf & Horwitz, 1992; Drach et al ., 1996) that are released after administration of LPS may inhibit P‐gp‐mediated drug transport, especially at the earlier time points. Lastly, LPS may also decrease P‐gp transport activity through protein kinase‐mediated phosphorylation of P‐gp (Miller et al ., 1998; Tepperman et al ., 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2001) demonstrated that the pentoxyfilline (an inhibitor of TNF‐ α production) prevented the loss in biliary elimination of rhodamine123 after administration of K. pneumoniae endotoxin. Alternatively, endogenous compounds that are substrates for P‐gp including inflammatory cytokines and corticosterone (Wolf & Horwitz, 1992; Drach et al ., 1996) that are released after administration of LPS may inhibit P‐gp‐mediated drug transport, especially at the earlier time points. Lastly, LPS may also decrease P‐gp transport activity through protein kinase‐mediated phosphorylation of P‐gp (Miller et al ., 1998; Tepperman et al ., 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the expression of P‐gp may be important in the immune response (Panwala et al ., 1998; Johnstone et al ., 2000). P‐gp and members of the oatp family transport endogenous molecules, which are involved in inflammation including steroids, leukotrienes, prostaglandins and cytokines (Schinkel et al ., 1995; Drach et al ., 1996; Meijer et al ., 1998). It should be a priority to investigate if the loss in expression of these transporters in the brain and liver are important for regulating the body disposition of inflammatory/antiinflammatory mediators during episodes of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Miscellaneous ABC transporters may have different function. For instance, P‐glycoprotein has been reported to be involved in the natural killer and T cell mediated cytotoxicity (11, 12) and in the transport of cytokines (13). MRP1, unlike P‐glycoprotein, facilitates the secretion of leukotrienes, the major mediators of inflammation (14).…”
Section: Discussionmentioning
confidence: 99%
“…it was suggested that IL-2 itself can be transported by P-gp. 30 The question is how P-gp could contribute to the uncontrolled growth of the gingiva. This hyperplasia is caused by modifications of the extracellular matrix components, particularly collagen.…”
Section: Discussionmentioning
confidence: 99%